Association between concurrent genital bleeding and cervical cancer: a cross‐sectional study. (17th June 2015) - Xavier‐Júnior, José C.C.; Vale, Diama B.; Zeferino, Luiz C.; dufloth, Rozany M.
Abstract Introduction Genital bleeding may be a common symptom among women with cervical cancer. Material and methods Cross‐sectional study evaluating whether the prevalence of cervical smear results is different in women with and without clinical information about concurrent genital bleeding. Results The sample consisted of 2 324 836 smears; of these, 0.4% had clinical information on genital bleeding. When stratified by age group, women with genital bleeding had a higher chance of a cytological result of a high‐grade squamous intraepithelial lesion [30–49 years odds ratio (OR) 2.38; 95% confidence interval (CI) 1.60–3.53 and ≥50 years OR 6.30; 95%CI 3.72–10.67), of squamous cell carcinoma (SCC) (30–49 years OR 24.70; 95%CI 11.96–51.03 and ≥50 years OR 48.91; 95%CI 31.28–76.47) and of atypical glandular cells (30–49 years OR 5.72; 95%CI 3.30–9.93 and ≥50 years OR 11.56; 95%CI 5.96–22.45); there was also a higher chance of adenocarcinoma for women ≥50 years (OR 53.13; 95%CI 28.08–100.51). The sensitivity of genital bleeding for women aged 18–29 years was 0.4% for high‐grade squamous intraepithelial lesion (HSIL); for women 30–49 years old the rate was 0.9% for HSIL, 8.6% for SCC and 2.1% for atypical glandular cells of undetermined significance (AGUS), while for women aged from 50 years or more the rates were 2.0% for HSIL, 13.7% for SCC, 3.6% for AGUS and 14.7% for adenocarcinoma. Conclusion Women ≥30 years old with genital bleeding should be referred for colposcopy to rule out the possibility of cervical cancer.